Co-ingestion of Antioxidant Drinks With an Unhealthy Challenge Meal Fails to Prevent Post-prandial Endothelial Dysfunction: An Open-Label, Crossover Study in Older Overweight Volunteers - Muggeridge, David J. (Front Physiol, 2019)
Eating a high calorie meal is known to induce endothelial dysfunction and it is reported that consuming drinks rich in antioxidants may be protective against this. In this study we assessed the effects of three antioxidant drinks with considerable disparity in their antioxidant content on endothelial function. Seven apparently healthy overweight and older adults (BMI 25–35; mean age 57 ± 3 years; one male, six females) completed four trials in a randomized counterbalanced design. Water (control), orange juice, green tea, or red wine were consumed with a high calorie meal (>900 kcal). Endothelial function was measured by flow-mediated dilatation immediately before (fasted, baseline) and 2 h after the meal. Blood samples were also obtained for lipid and glucose analysis, plasma nitrite ([Formula: see text]) and oxidized low-density lipoprotein (ox-LDL). Participants returned after a minimum 3 days washout to complete the remaining arms of the study. The results found that the high calorie meal induced a substantial increase in triglycerides, but not cholesterol or glucose, at 2 h after meal ingestion. FMD was significantly reduced by ∼35% at this timepoint, but the effect was not attenuated by co-ingestion of any of the antioxidant drinks. Reduced FMD was mirrored by a reduction in [Formula: see text] , but ox-LDL was not increased at 2 h after the meal. None of the undertaken measures were influenced by the antioxidant drinks. We conclude that co-ingestion of none of our test antioxidant drinks protected against the substantial post-prandial endothelial dysfunction induced by an unhealthy meal challenge in our sample population at a 2 h timepoint.